Effect of Others Comprehensive Income on Company Value by Mediation of Retained Earnings: Evidence From Indonesia - Athori, Agus; Kusuma, Marhaendra (JCA (Jurnal Cendekia Akuntansi), 2023)
Research so far has only tested the effect of other comprehensive income (OCI) and retained earnings on firm value separately. Not many studies have examined the effect of OCI on retained earnings and the mediating role of retained earnings in it’s effect on firm value. This test is important to do as proof of the relevance value of group OCI items that will not be reclassified to net income, where their age as unrealized income is longer than other group OCI items.Test results on the market in Indonesia show: (1) OCI of groups that will not be reclassified to net income has a significant positive effect on retained earnings, but not on firm value, and (2) retained earnings mediate the effect of OCI of groups that will not be reclassified to net income to company value. Retained earnings represent accumulated earnings for the past period including accommodating income from OCI realization which was previously presented as a group that will not be reclassified to net income, which eventually these items become part of retained earnings, including OCI items for the closest period whose amount and time of realization are not known for certain in the end will also become part of retained earnings. The originality of this research is to test the influence of: (1) OCI on retained earnings and (2) mediation of retained earnings in the effect of OCI on firm value.